(untitled) (LTU Journal of Advanced Computing & Engineering, 2026)
This study investigates the static axial load behaviour of bored cast-in-situ pile foundations through three-dimensional numerical simulation using site-specific geotechnical data obtained from the Kamal Khola Bridge under the SASEC Highway Enhancement Project, Nepal. Although static load testing (SLT) provides reliable pile performance assessment, it is often time-consuming and costly; therefore, this research evaluates the applicability of finite element modelling using PLAXIS 3D as an efficient and economical alternative. Detailed subsurface characterization, including borehole logs, standard penetration test (SPT) data, and engineering soil parameters at the pier location, was incorporated into the numerical model. The soil was simulated using the Mohr–Coulomb constitutive model, while the pile was modelled as a linear elastic material. A mesh sensitivity analysis was conducted using very fine, fine, medium, coarse, and very coarse mesh configurations to examine their influence on prediction accuracy. The numerical results were validated against field SLT data comprising load–settlement responses, initial and final settlements, and elastic rebound measurements. The comparison demonstrated strong agreement between simulated and measured responses, with percentage differences in allowable load ranging from 9.7% to 11.8% and settlement variations between 2.2% and 13% across different mesh refinements. Additionally, a comparative assessment of testing time and cost revealed that numerical simulation reduced overall duration and expenditure by approximately 58.33% and 66.67%, respectively, compared to field SLT. The findings confirm that PLAXIS 3D can reliably replicate field pile load behaviour and serve as a practical verification tool, enabling economical, time-efficient, and safe foundation design practices under Nepalese soil conditions.